Peranan Kredit Usaha Rakyat (KUR) Terhadap Kinerja UMKM di Kabupaten Jembrana - Mayuni, Made Ary; Rustariyuni, Surya Dewi (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Improved performance of SMEs hit by a variety of obstacles and challenges in the face of competition. Lack of capital is owned SMEs is challenge faced today. SME entrepreneurs difficulty to obtain loan capital because it does not have sufficient assets to meet the requirements of the loan at the bank. To address the problem, the government issued a policy in the form of loan program for SMEs with a guarantee that the pattern of KUR. KUR is expected to help SMEs to increase business capital, so that business performance can be improved. The aim of this study was to determine differences in the production, labor, earning and cost of SMEs before and after using the KUR. This research was conducted in Jembrana with the of amount sample was 382 respondents. The method used observation, questionnaire and  interviews. This research uses different test that Wilcoxon to see the difference in performance of SMEs before and after using the KUR of BRI. The result showed that the performance of SMEs seen from production variables, variable labor, variable income and variable cost in Jembrana increased. SME entrepreneurs can improve their business performance after getting assistance from BRI KUR. From the results obtained , it is expected there are the role of financial institutions ,the Department of Labor, Department of Industry, Trade and Cooperatives to improve the performance of SMEs and SMEs entrepreneurs are expected to add to the labor cost of treatment to ensure the safety of workers.
Keywords: KUR, SMEs , performance, production , employment , cost.